Comparison study of the influence of carbon and halloysite nanotubes on the preparation and rheological behavior of linear low density polyethylene - Burzynski, Maksymilian; Sandra; Elżbieta; Izabela; Kamil; Anna; Stanisław; Jakub (Polimery, 2020)
Two 1D-types’ nanofillers, in the form of multi-walled carbon nanotubes (MWCNTs) and halloysite nanotubes (HNTs), were introduced in an amount of 10, 15 and 20 wt % to linear low density polyethylene (LLDPE) in order to compare their effect on rheological properties. The neat LLDPE and its nanocomposites were obtained by direct melt blending. Since rheological properties have a key impact on the processing of polymer materials, it has been determined whether and how carbon and non-carbon nanotubes affect the viscosity of the composition. It was found that the addition of MWCNTs more significantly affects both the melt viscosity as well as the storage and loss moduli of the LLDPE matrix, compared to HNTs-based nanocomposites.